TRUST BASED ROUTING ALGORITHM IN INTERNET OF THINGS (IoT) - Raj, Jennifer S.; S, Alphina Stephy. (IRO Journal on Sustainable Wireless Systems, 2019)
The development in the area of networking is Internet of Things (IoT). This will interrelated the object and things together. The realization of IoT subsystems will be subjected to numerous constraints that include cost, power, energy, and lifetime. However, most challenging requirement will be trust. It is widely recognized that the attacks from malicious parties can activate from Internet to the physical word. Hence, trust of IoT is of essential importance. Therefore, trust management is considered as a efficient solution to IoT related issues. Trust management has useful technology for providing security service and it has been used in many applications such as P2P, Grid, adhoc network and so on. Thus the trust based routing algorithm in Internet of Things is proposed for providing a potential security system. With this, the major focus on the problem of trust on the malicious nodes in any environment.
Keywords: Internet of Things; sensor; malicious nodes